TRANSPORTE DE POLEN POR APIS MELLIFERA EN LA PAMPA DEL TAMARUGAL (Acta Entomológica Chilena, 2022)
Apis mellifera acts as a good potential pollinator of Prosopis tamarugo in the desert part ofChile. Several colonies have been carried over to the Pampa del Tamarugal during the bloomingseason, in order lo increase the productivity of honey. About 10 per cent of the foragers show fullpollen loads, bolh in winter and spring time; almost all of the foragers observed carned pollen on theclypeus and sternal thoracic hairs. Wild colonies were in very poor conditions, presenting noadaptations lo the xeric environment. The floral biology of P. tamarugo shows interesting featuresthal are betler understood under the Bateman’s Principie.